Estudio de pre factibilidad para la instalación de una planta productura de cervezas artesanales en toneles para bares de Lima Metropolitana - Heredia Andújar, Grace (2016)
The research presented was aimed to establishing market, technical, economic and financial viabiliity of implementing a craft beer manufacturing plant in Lima. This industry has develope with huge successl in countries with more developed beer culture as USA, Germany, Colombia or Chile. In Peru it is still in an embryonic stage.